Clinical Features of Nephrotic Syndrome in Children - M.P. Damanik (Indonesian Pediatric Society, 1997)
We reviewed 129 new patients with primary nephrotic syndrome (PNS) admitted to the Department of Child Health Sardjito Hospital from January 1986 to December 1995. Most patients were males, i.e., 96 or 74.4%, giving a male to female ratio of 2,9:1. The number of patients under die age of 6 years was 66 (or 51.2%), slightly greater than the number of patients over the age of 6 years (63 patients, or 48.8%). Nephritic symptoms consisting of hematuria, hypertension and azotemia were more frequently found in patients over the age of 6 years, and in non-responder patients. With prednisone treatment, 108 (Or 83.7%) of patients were steroid responÂders, and 21 (or 16.3%) were non-steroid responder.